2015
DOI: 10.1016/j.apm.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the exponentiated half logistic distribution

Abstract: In this paper moment estimators and maximum likelihood estimators of unknown parameters in the exponentiated half-logistic distribution are derived, and an entropy estimator is obtained for the distribution. An exact expression of Fisher information is derived to obtain approximate confidence intervals for unknown parameters in the distribution, and for illustration purposes, the validity of the proposed estimation method is assessed using real data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Due to its wide application, the model has attracted several authors to propose its extension for added flexibility in modeling, for example, generalized half logistic (GHL) [14], power half logistic (PwHL) [15], Olapadehalf logistic (OHL) [16] etc. Among them, we are interested in the two-parameters generalized half logistic distribution, some statistical studies and usefulness of the GHL can be found in [17].…”
Section: The Poighl Model and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its wide application, the model has attracted several authors to propose its extension for added flexibility in modeling, for example, generalized half logistic (GHL) [14], power half logistic (PwHL) [15], Olapadehalf logistic (OHL) [16] etc. Among them, we are interested in the two-parameters generalized half logistic distribution, some statistical studies and usefulness of the GHL can be found in [17].…”
Section: The Poighl Model and Propertiesmentioning
confidence: 99%
“…The measures md 1 (x) and md 2 (x) can be calculated using the relationship J(.). By considering (17) we have…”
Section: Mean Deviations Bonferroni and Lorenz Curvesmentioning
confidence: 99%
“…In this section, We consider a real dataset. This dataset from [9] This dataset has been previously analyzed by [16] etc. Here we fit the dataset with generalized inverted half-logistic distribution.…”
Section: Real Illustrative Examplementioning
confidence: 99%
“…respectively. [17] discussed some important properties and application of the generalized half logistic distribution. [18] investigated the estimation of multicomponent stressstrength reliability based on generalized half logistic.…”
Section: Introductionmentioning
confidence: 99%